Creación y regulación de un estado civil de separados para que los cónyuges no divorciados puedan adquirir créditos y obligaciones personales. - Vásquez Cabrera, Rosa Magaly (2023)
This Curricular Integration Work is focused on the investigation and analysis of a current issue where individuals who are married or in a common-law relationship, after being legally recognized as such, form a joint property society. However, within these respective households, whether stemming from marriage or common-law union, legal conditions arise that directly impact the social and economic development of each of the parties involved, such as separation or abandonment without divorce or dissolution of the marital partnership. These separated couples cannot increase their personal assets or obtain personal credit. The conducted study reveals that couples who are separated without dissolving the marital partnership or divorcing cannot obtain personal credit or engage in personal transactions because they are still legally engaged to a marriage or common-law union. This is a legal gap, a legal issue that has not been regulated by the law. Therefore, it is necessary to establish a civil status for separated individuals. Considering that civil statuses are not permanent but temporary, the regulation of the civil status of separated individuals will serve to dissolve the marital partnership, even if the parties do not divorce. This will enable these individuals to obtain credit on their own, without the authorization of their spouse or partner, and to sell their assets without their spouse's authorization. In this research, materials and methods were used to facilitate the research process. Surveys and interviews with legal professionals were conducted, and the results were used to propose a legal reform project to amend the Civil Code and Notarial Law. This reform aims to incorporate the civil status of "separated," which can be obtained through a specific citation process defined in the COGEP (Code of General Organic Processes) followed by a voluntary procedure before a notary. The resulting resolution will then be registered in the corresponding civil registry. Importantly, this decision will not affect or alter the property society of the other spouse but will apply to future matters. In all other aspects, the dissolution, inventory, and partition process will be followed if deemed necessary by the previous spouse.